DNA barcoding of Cymbidium by genome skimming: Call for next‐generation nuclear barcodes. (4th November 2022) - Zhang, Le; Huang, Yi‐Wei; Huang, Jia‐Lin; Ya, Ji‐Dong; Zhe, Meng‐Qing; Zeng, Chun‐Xia; Zhang, Zhi‐Rong; Zhang, Shi‐Bao; Li, De‐Zhu; Li, Hong‐Tao; Yang, Jun‐Bo
Abstract: Cymbidium is an orchid genus that has undergone rapid radiation and has high ornamental, economic, ecological and cultural importance, but its classification based on morphology is controversial. The plastid genome (plastome), as an extension of plant standard DNA barcodes, has been widely used as a potential molecular marker for identifying recently diverged species or complicated plant groups. In this study, we newly generated 237 plastomes of 50 species (at least two individuals per species) by genome skimming, covering 71.4% of members of the genus Cymbidium . Sequence‐based analyses (barcoding gaps and automatic barcode gap discovery) and tree‐based analyses (maximum likelihood, Bayesian inference and multirate Poisson tree processes model) were conducted for species identification of Cymbidium . Our work provides a comprehensive DNA barcode reference library for Cymbidium species identification. The results show that compared with standard DNA barcodes ( rbcL  +  matK ) as well as the plastid trnH ‐ psbA, the species identification rate of the plastome increased moderately from 58% to 68%. At the same time, we propose an optimized identification strategy for Cymbidium species. The plastome cannot completely resolve the species identification of Cymbidium, the main reasons being incomplete lineage sorting, artificial cultivation, natural hybridization and chloroplast capture. To further explore the potential use of nuclear data in identifying species, the Skmer method was adopted and the identification rate increased to 72%. It appears that nuclear genome data have a vital role in species identification and are expected to be used as next‐generation nuclear barcodes.